Everyday Chinese Speaking Proficiency Guidelines: A Case Study of Chulalongkorn University Students - Pichetsilpa, Pattra (Journal of Sinology (วารสารจีนวิทยา), 2007)
This article is to study and propose a Chinese speaking proficiency guidelines for Thai students using Chulalongkorn University’s Chinese-majored students as a case in focus. In our analysis of each course in the curriculum of Chulalongkorn University Chinese Language Major, we first apply the so - called Language Functional Trisection, as developed by the American Council on the Teaching of Foreign Languages ( ACTFL ) to help summarize students ’ expected speaking ability on each subject and to determine to which level each subject should belong. Next we compare ACTFL Chinese speaking proficiency guidelines to those of Chulalongkorn University from two different aspects; horizontal and vertical. Our finding shows that in all levels not only is the speaking ability of Chulalongkorn University students majoring in Chinese higher than that of ACTFL’s, their level of progression grows faster than that of ACTFL’s as well.